Sociocultural and demographic factors associated with quality of life in adults with chronic non-communicable diseases - Amador, Yanedsy Díaz; Cedeño, Nohelia Romina Robinson; Rodríguez, Maykel Soto (Journal of Posthumanism, 2025)
The present study aimed to determine the association between sociocultural and demographic factors and quality of life in adults with chronic non-communicable diseases. The participants were 256 adults aged 20 to 64 years, of both sexes, who attended the Dr. Liborio Panchana General Hospital, Ecuador. The sample consisted of 155 adults, selected by simple random method, during the year 2024. A quantitative, descriptive, cross-sectional approach was used, with a non-experimental correlational level. The results were processed using the statistical program SPSS, version 27. The mean age of older adults was 51.2 ± 56.4 years, 52.25% were women, and a significant association was found in age, level of academic education, type of housing construction, essential basic services and monthly economic income (p < 0.05). It is concluded that sociocultural and demographic factors are associated with the quality of life of adults with NCDs.